Facial emotion recognition and the development of delinquency: the mediating role of social bonds and self-control - Chae, Young Ju (Psychology, crime & law, 2022)
Although facial emotion recognition has been identified as a potential factor influencing life-course-persistent delinquency, the mechanism underlying this relationship remains largely unknown. In this study, we explored two key variables—social bonds and self-control—as parallel mediators in the relationship between facial emotion recognition and general delinquency. An integrated design was employed using the models of social selection and social causation in criminology and the theory of attachment and conceptually parallel theories and research in psychology. The data came from a three-wave nationally representative longitudinal study of 1,423 children and adolescents carried out in the U.S. As expected, faces expressing anger and happiness were associated with general delinquency over 5 years, and both social bonds and self-control significantly mediated the associations. The accurate recognition of anger cues increased engagement in delinquent behavior by lowering both social bonds and self-control levels. In turn, the increased recognition of happy cues reduced delinquent behavior by enhancing both social bonds and self-control levels. Findings underscore the importance of identifying mediating pathways between facial emotion recognition and delinquency and suggest that these pathways are a potential target for behavioral intervention.